Penatalaksanaan Fisioterapi Pada Pasien Stroke Hemoragik Di Roujin Home Jepang - Gandi, Febrianti Sonia; Apriliyani, Ita; Utami, Tin (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2024)
Stroke is the third leading cause of death in the world after coronary heart disease and cancer in both developed and developing countries (Hasan, 2018). Hemorrhagic stroke is a disease caused by rupture of blood vessels around or inside the brain, so that the blood supply to the brain tissue will be blocked. The broken blood can flood the surrounding brain tissue, so that brain function will be disrupted (Kanggeraldo, Sari, and Zul 2018). The purpose of this study was to evaluate the impact of physiotherapy given to the healing process of hemorrhagic stroke patients. This research uses a descriptive case study method on individuals with hemorrhagic stroke. In this study using purposive sampling with the following criteria: adult age, diagnosis of hemorrhagic stroke, nursing problems related to physical mobility disorders and willingness to participate in this study. The study was conducted on January 02-04, 2023 at iryou houjin aiwa ikeda en aiwa deikea room. The instruments used in this study were observation and interviews with patients and therapists. This study was conducted on one patient who experienced hemorrhagic stroke on the left side of the body. Research conducted for 3 days obtained the results that the effect of massage given by the therapist had an effect of 60% in training and relaxing the patient's muscles and joints. While the effect of the motion exercises given was 70% in the process of improving the patient's mobility.